Perancangan UI/UX Menggunakan Metode UCD Pada Website PMKS Pendataan Anak Yatim Lombok Tengah - Rizkina, Ria (Jurnal Ilmiah IKIP Mataram, 2023)
The design of User Interface (UI) and User Experience (UX) for an orphanage care application plays an important role in providing a good user experience and meeting their needs. Therefore, the purpose of this research is to create an orphanage care application that is suitable for the needs and desires of users. The research methodology used is by conducting direct interviews with users and observing similar applications. The results of the study show that users want an application that is easy to use, has an attractive appearance, and useful features. In addition, data security and accessibility must also be considered in designing the application. The final result of this research is a prototype of an orphanage care application with UI/UX that can help users meet their needs easily and enjoyably